2013
DOI: 10.1186/1472-6963-13-410
|View full text |Cite
|
Sign up to set email alerts
|

The health outcomes and costs of people attending an interdisciplinary chronic disease service in regional Australia: protocol for a longitudinal cohort investigation

Abstract: BackgroundRates of chronic disease are escalating around the world. To date health service evaluations have focused on interventions for single chronic diseases. However, evaluations of the effectiveness of new intervention strategies that target single chronic diseases as well as multimorbidity are required, particularly in areas outside major metropolitan centres where access to services, such as specialist care, is difficult and where the retention and recruitment of health professionals affects service pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Investigation of pragmatic aspects of RAPaRT implementation may include determining the most efficient (and reliable) method of completing the instrument, where self-administration, proxy administration, health professional administration or administration by an allied health assistant are worthy of consideration 20. The impact on health service outcomes (including patient flow, volume and timing of referrals), as well as patient outcomes,21 from implementing the RAPaRT in emergency health services, are also important future research directions. This may include evaluation of the clinical and economic impact of using a single positive response to trigger a referral versus two or more positive responses based on real life clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of pragmatic aspects of RAPaRT implementation may include determining the most efficient (and reliable) method of completing the instrument, where self-administration, proxy administration, health professional administration or administration by an allied health assistant are worthy of consideration 20. The impact on health service outcomes (including patient flow, volume and timing of referrals), as well as patient outcomes,21 from implementing the RAPaRT in emergency health services, are also important future research directions. This may include evaluation of the clinical and economic impact of using a single positive response to trigger a referral versus two or more positive responses based on real life clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The psychometric properties of the SF-36 relevant to this study for people with chronic disease have been reported elsewhere. 16 The SF-36 dimensions were scored on a 0 to 100 percentage scale with 0 indicating the worst health state and 100 the best health state. Four dimensions (physical functioning, role-physical, bodily pain and general health) have been found to cluster most strongly on a physical component of HRQoL and four dimensions (vitality, social functioning, role-emotional, mental health) have been found to cluster most strongly on a mental component of HRQoL.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, this study will provide insights into how to better provide health care services for Aboriginal people in rural and remote communities. The findings will also contribute to the broader literature of rural and remote health service provision [ 30 ] and provide recommendations for future practice, which if adopted could lead to improvement of population health services.…”
Section: Discussionmentioning
confidence: 94%